PENGEMBANGAN VIDEO POLA LANTAI TARI SERIMPI BERBASIS ARTIFI-CIAL INTELLIGENCE PADA PEMBELAJARAN GEOMETRI SISWA KELAS V SEKOLAH DASAR - Siti Mufaroha; Cicilia Ika Rahayu Nita; Andika Gutama (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to develop an Artificial Intelligence (AI)-based animated video learning medium that integrates ethnomathematics concepts through the floor patterns of the Serimpi Dance in geometry material for elementary school students. The background of this research is the low visualization ability of students towards abstract geometry concepts and the sub-optimal utilization of digital technology in the learning process. The research method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research subjects involved media experts, material experts, and language experts as validators, as well as fifth-grade elementary school students for product trials. Data collection instruments included validation questionnaires, observations, and learning outcome tests (pretest and posttest). The results showed that: (1) The AI-based animated video learning medium was declared highly feasible with a validity percentage of 95% from media experts, 87.5% from material experts, and 87.5% from language experts. (2) This learning medium is effective in improving student learning outcomes, as evidenced by the increase in the average score from 58.28 in the pretest to 91.03 in the posttest. (3) The N-Gain analysis of 77.93% indicates that this medium is in the